2014
DOI: 10.1007/s10658-014-0483-9
|View full text |Cite
|
Sign up to set email alerts
|

Early PCR-based detection of Fusarium culmorum, F. graminearum, F. sporotrichioides and F. poae on stem bases of winter wheat throughout Poland

Abstract: Foot rot and crown rot are fungal diseases of wheat caused by a complex of Fusarium species. They have a huge economic impact mainly due to yield reduction. A survey was conducted to identify four Fusarium species, occurring on wheat stem bases, using speciesspecific PCR assays in samples collected during spring of 2012. The dominant species was F. graminearum, which was identified in above 64 % of samples. F. culmorum was detected in 15.71 %, F. poae in 15.71 % and F. sporotrichioides in 5.71 % wheat fields. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 48 publications
1
11
0
1
Order By: Relevance
“…Interestingly, both F. graminearum and F. culmorum were isolated (PVS-Fu 426 and 432; PVS-Fu 428 and 435) from two heads collected in 2013 from the same field (Table 2). This confirms the potential role of co-infection as shown in Poland in a recent survey (Kuzdrali nski et al, 2014) where F. graminearum is the major component of stem disease colonization also able to favour its association with F. culmorum. The only F. cortaderiae isolate from Sardinia was associated with FHB.…”
Section: Discussionsupporting
confidence: 87%
“…Interestingly, both F. graminearum and F. culmorum were isolated (PVS-Fu 426 and 432; PVS-Fu 428 and 435) from two heads collected in 2013 from the same field (Table 2). This confirms the potential role of co-infection as shown in Poland in a recent survey (Kuzdrali nski et al, 2014) where F. graminearum is the major component of stem disease colonization also able to favour its association with F. culmorum. The only F. cortaderiae isolate from Sardinia was associated with FHB.…”
Section: Discussionsupporting
confidence: 87%
“…Another complex disease of wheat caused by a group of Fusarium species is foot and crown rot. Overall, four species of the pathogen ( Fusarium graminearum, F. culmorum, F. poae, and F. sporotrichioides ) are associated with the disease although their prevalence differs from one geographic region to another ( Kuzdraliński et al, 2014 ). It has also been reported that the majority of fields in eastern Poland are subjected to the attack of at least one or two of Fusarium species.…”
Section: Synergistic Pathogen–pathogen Interactionsmentioning
confidence: 99%
“…In addition, a negative correlation between F. graminearum and F. langsethiae was observed (-0.39). The interaction between Fusarium species was studied by Kuzdraliński et al (2014) on stem bases of winter wheat derived from different regions of Poland (eastern, central, south-western and north-western Poland) in 2012. In that study, it was proved that the presence of F. graminearum was related to the presence of F. culmorum (0.324), and the occurrence of F. poae was associated with F. sporotrichioides (0.26) on stem bases of winter wheat.…”
Section: Data Analysesmentioning
confidence: 99%
“…PCR can be an alternative or a complement to the identification based on morphological characteristics (Demeke et al 2005;Spanic et al 2010;Faria et al 2012;Suga et al 2013). The most frequently identified species by PCR are F. graminearum and F. culmorum (Kuzdraliński et al 2014). In addition, there is a number of molecular methods to identify other species of Fusarium, e.g., F. sporotrichioides, F. poae, F. avenaceum, F. proliferatum, F. oxysporum, F. verticillioides, F. equiseti, F. fujikuroi or F. acuminatum (Mishra et al 2003;Demeke et al 2005;Amatulli et al 2010).…”
Section: Introductionmentioning
confidence: 99%